Succinic acid as a coordination modulator for DMSO-free low-dimensional red-emitting tin perovskites - Akhil Sreevalsan; Woo Hyeon Jeong; Yifan Yu; Cheong Beom Lee; Gunhee Kim; Jongbeom Kim; Hochan Song; Hong In Jeong; Gyeong Eun Seok; Dong-Won Kang; Myoung Hoon Song; Kyeounghak Kim; et al. (Chemical Engineering Journal, 2026)

Reducing greenhouse gas emissions while improving rice yield and water use efficiency in rice paddies through mid-season drainage and intermittent irrigation - Su-Heon Jang; Jae-In Lee; Chang-Gu Lee; Gil Won Kim; Jin-Kyung Hong; Seong-Jik Park (Agriculture, Ecosystems & Environment, 2026)

Bioactive fibrous microwell platforms induce m1 macrophage clusters that enhance anti-tumor activity and T cell polarization - Juhwan Choi; Yongpyo Hong; Chungmo Heo; Eunji Yeom; Taehyeon Kim; In Seok Moon; Won-Gun Koh (Chemical Engineering Journal, 2026)

Ubiquilin 1 Inhibits intracellular proliferation of Salmonella enterica serovar Typhimurium through Xenophagy - In Sook Jeon; Yong-Hee Lee; Jin Tae Hong; Won Seop Kim; Jae-Cheon Shin; Hak-Kyo Lee; Joong-Kook Choi (Genes & Genomics, 2026)

Effects of web-based behavioral intervention on fine particulate matter, pulmonary function, and airway inflammation in children: The COCOA randomized controlled trial - Dirga Kumar Lamichhane; Bo-Mee Kim; Jungyun Bae; Hea Young Oh; Dong In Suh; Youn Ho Shin; Kyung Won Kim; Kangmo Ahn; Hyo-Bin Kim; Song-I Yang; So-Yeon Lee; Soo-Jong Hong; et al. (Environmental Research, 2025)

Improving acid-free and selective leaching of lithium from end-of-life LiFePO4 batteries using sodium persulfate: Impact of removing organic matter by thermal treatment in an inert atmosphere - Jong-Won Choi; Mooki Bae; Hyunju Lee; Hong-In Kim; Hyun-Woo Shim; Jinyoung Je; Gigap Han; Junhyun Choi; Hyunjoon Lee; Sookyung Kim (Hydrometallurgy, 2025)

Spatiotemporally adjustable hybrid hydrogels interconnected by 2D MXene for combinatorial therapy of infected diabetic wounds - Mrinmoy Karmakar; Sungyun Kim; Han-Jun Kim; Ji Won Huh; Da In Jeong; Eunseo Park; Seongeun Kim; Eun-Hye Hong; Jin Hyeong; Dae-Joon Kim; Hye Kyu Choi; Junmin Lee; et al. (Chemical Engineering Journal, 2025)

Preclinical Pharmacokinetics of DM5167, a Novel Selective PARP1 Inhibitor - Jin Woo Kim; Seung-Won Lee; Myung Eun Jung; Ki-Hong Jang; Hae-In Choi; Yoon Ha Lee; Jeongmin Kim; Sunjoo Ahn; Eunhee Kim; Tae-Sung Koo (Pharmaceutical Research, 2025)

AI-driven multivariate time series forecasting of transmembrane pressure in ultrafiltration: A stationarity-aware approach - Dongju Kim; Jong Pil Yun; Taehan Lee; Daewoong Jung; Hong-In Won (Journal of Water Process Engineering, 2025)

Machine learning-driven discovery of innovative hybrid solid electrolytes for high-performance all-solid-state batteries - Ji-Hwan Kim; Jiwon Sun; Juo Kim; Ji-Min Hong; Seungpyo Kang; Jinyoung Jeong; Eunsong Kim; Deok-Hye Park; Jae-Sung Jang; Jong-Won Lim; Gang-In Lee; Kyoungmin Min; et al. (Chemical Engineering Journal, 2025)

PM exposure during pregnancy affects childhood asthma via placental epigenetic changes: Neuronal differentiation and proliferation and Notch signaling pathways - Hyo-Bin Kim; Si Hyeon Lee; Dae Yeol Yang; Seung-Hwa Lee; Jeong-Hyun Kim; Hwan-Cheol Kim; Kil Yong Choi; So-Yeon Lee; Song-I Yang; Dong In Suh; Youn Ho Shin; Kyung Won Kim; et al. (Environmental Pollution, 2025)

Ultrathin silica-encapsulated perovskite nanocrystals for high color purity mechanoluminescence - Kyung Sik Yoo; Hong In Jeong; Sujoy Bandyopadhyay; Seo-Jin Ko; Dong-Won Kang; Jihoon Lee; Hyosung Choi (Chemical Engineering Journal, 2024)

Solution-processed nanoporous and faceted CuO electrocatalyst for enhanced solar-to-hydrogen and nitrate-to-ammonia production - Runfa Tan; Min Je Kang; Li Qu; Sung Won Hwang; Seo Yeong Hong; Yoo Jae Jeong; Hyun Soo Han; Dong Hoe Kim; Sangwook Lee; In Sun Cho (Journal of Water Process Engineering, 2024)

Efficient full-color daytime radiative cooling with diffuse-reflection-dominant cholesteric liquid crystals - Sangwok Bae; Minjeong Kim; Gumin Kang; Hong-Sub Lee; In Soo Kim; Suk-Won Choi; Jin Gu Kang (Chemical Engineering Journal, 2024)

Coinfection with porcine epidemic diarrhea virus and Clostridium perfringens type A enhances disease severity in weaned pigs - Duri Lee; Guehwan Jang; Kyeng-Cheol Min; Inn Hong Lee; Hokeun Won; In-Joong Yoon; Sang Chul Kang; Changhee Lee (Archives of Virology, 2023)

Deletion of pentad residues in the N-terminal domain of spike protein attenuates porcine epidemic diarrhea virus in piglets - Guehwan Jang; Kyeng-Cheol Min; Inn Hong Lee; Hokeun Won; In-Joong Yoon; Sang Chul Kang; Changhee Lee (Veterinary Microbiology, 2023)

The optimal standard protocols for whole-genome sequencing of antibiotic-resistant pathogenic bacteria using third-generation sequencing platforms - Tae-Min La; Ji-hoon Kim; Taesoo Kim; Hong-Jae Lee; Yoonsuk Lee; Hyunjin Shin; Yongjun Song; Gyuhee Ahn; Won Hur; Joong-Bok Lee; Seung-Yong Park; In-Soo Choi; et al. (Molecular & Cellular Toxicology, 2021)

Assessment of the abuse potential of methamnetamine in rodents: a behavioral pharmacology study - Dong-Hyun Youn; Jin Mook Kim; Young-ki Hong; Seo-In Park; Jin-Moo Lee; Young-Hoon Kim; Chang Won Park; Mi Sun Kang (Psychopharmacology, 2021)

Corneal Repair with Adhesive Cell Sheets of Fetal Cartilage-Derived Stem Cells - In-Su Park; Byeong Kook Kim; Minh-Dung Truong; Hong Seok Yang; Sang-Hyug Park; Hyo Soon Park; Byung Hyune Choi; Bae Hie Won; Byoung-Hyun Min (Tissue Engineering and Regenerative Medicine, 2021)

Tomato hairless on stems mutant affects trichome development - Won-Ki Hong; Jae-In Chun; Na-Rae Jeong; Heejin Kim; Jin-Ho Kang (Horticulture, Environment, and Biotechnology, 2021)

Health risk assessment for multimedia exposure of formaldehyde emitted by chemical accident - Si-Hyun Park; Hui-Been Lim; Hyong-Jin Hong; Hee-Seok Kim; Dan-Ki Yoon; Hye-Won Lee; Hye-Kwan Kong; Jeong-In Jeon; Ji-Won Choi; Eun-Min Cho; Yong-Sung Cho; Cheol-Min Lee (Environmental Science and Pollution Research, 2021)

Vildagliptin, an Anti-diabetic Drug of the DPP-4 Inhibitor, Induces Vasodilation via Kv Channel and SERCA Pump Activation in Aortic Smooth Muscle - Mi Seon Seo; Hongliang Li; Jin Ryeol An; In Duk Jung; Won-Kyo Jung; Kwon-Soo Ha; Eun-Taek Han; Seok-Ho Hong; Il-Whan Choi; Won Sun Park (Cardiovascular Toxicology, 2019)

Correction to: Contribution of Zinc-Dependent Delayed Calcium Influx via TRPC5 in Oxidative Neuronal Death and its Prevention by Novel TRPC Antagonist - Sang Eun Park; Ji Hoon Song; Chansik Hong; Dong Eun Kim; Jee-Won Sul; Tae-Youn Kim; Bo-Ra Seo; Insuk So; Sang-Yeob Kim; Dong-Jun Bae; Mi-Ha Park; Hye Min Lim; et al. (Molecular Neurobiology, 2019)

Contribution of Zinc-Dependent Delayed Calcium Influx via TRPC5 in Oxidative Neuronal Death and its Prevention by Novel TRPC Antagonist - Sang Eun Park; Ji Hoon Song; Chansik Hong; Dong Eun Kim; Jee-Won Sul; Tae-Youn Kim; Bo-Ra Seo; Insuk So; Sang-Yeob Kim; Dong-Jun Bae; Mi-Ha Park; Hye Min Lim; et al. (Molecular Neurobiology, 2019)

Neuronal loss and gliosis in the rat striatum subjected to 15 and 30 minutes of middle cerebral artery occlusion - Joon Ha Park; Jeong Hwi Cho; Ji Hyeon Ahn; Soo Young Choi; Tae-Kyeong Lee; Jae-Chul Lee; Bich Na Shin; Seongkweon Hong; Yong Hwan Jeon; Young-Myeong Kim; In Koo Hwang; Young Joo Lee; et al. (Metabolic Brain Disease, 2018)

The assessment of droughts in Northern China and Mongolian areas using PDSI and relevant large‐scale environments - Jae‐Won Choi; In‐Gyum Kim; Jeoung‐Yun Kim; Baek‐Jo Kim; Cheol‐Hong Park; Do‐Woo Kim (International Journal of Climatology, 2016)
This study assessed drought conditions in northern China and Mongolian areas using the Palmer drought severity index ( PDSI ). Droughts in this area were intensified throughout all seasons. In particular, this intensifying trend was pronounced in the summer and autumn. In the summer, the PDSI showed an overall increase from the early 1990s to the late 1990s, and then, it rapidly decreased after the late 1990s. Therefore, this study focused on summer droughts and analysed mean differences before the late 1990s (9098) and after the late 1990s (9905). Regarding differences in 850 hPa stream flows between the two periods, anomalous anticyclonic circulations were strengthened in northern China and Mongolia that showed strong negative anomalies in the PDSI . These anomalous anticyclones were formed as a positive North Atlantic Oscillation pattern formed in the European region spread eastward in the form of wave trains. The anomalous anticyclones formed in northern China and Mongolia led to reduced total cloud cover. As a result, this region exhibited high sensible heat net fluxes. Consequently, warm and dry anticyclones may have recently been strengthened in this region, thereby intensifying droughts. As this shows, recently strengthened warm and dry anticyclones in northern China and Mongolia were associated with recently reduced snow depths in this region during the preceding spring. In recent years, the frequency of Asian dust has also increased due to warm and dry air conditions.

Inhibitory effect of snake venom toxin on NF-κB activity prevents human cervical cancer cell growth via increase of death receptor 3 and 5 expression - Hye Lim Lee; Mi Hee Park; Ji Eun Hong; Dae Hwan Kim; Ji Young Kim; Hyen Ok Seo; Sang-Bae Han; Joo Hee Yoon; Won Hyoung Lee; Ho Sueb Song; Ji In Lee; Ung Soo Lee; et al. (Archives of Toxicology, 2016)

Inhibition of Mitochondrial Clearance and Cu/Zn-SOD Activity Enhance 6-Hydroxydopamine-Induced Neuronal Apoptosis - Sua In; Chang-Won Hong; Boyoung Choi; Bong-Geum Jang; Min-Ju Kim (Molecular Neurobiology, 2016)

The role of APCDD1 in epithelial rearrangement in tooth morphogenesis - Sanjiv Neupane; Wern-Joo Sohn; Gi-Jeong Gwon; Ki-Rim Kim; Sanggyu Lee; Chang-Hyeon An; Jo-Young Suh; Hong-In Shin; Hitoshi Yamamoto; Sung-Won Cho; Youngkyun Lee; Jae-Young Kim (Histochemistry and Cell Biology, 2015)

Developmental regulations of Perp in mice molar morphogenesis - Sanjiv Neupane; Wern-Joo Sohn; Girdhari Rijal; Ye-Ji Lee; Sanggyu Lee; Hitoshi Yamamoto; Chang-Hyeon An; Sung-Won Cho; Youngkyun Lee; Hong-In Shin; Tae-Yub Kwon; Jae-Young Kim (Cell and Tissue Research, 2014)

Comparative transcriptomic analysis to identify differentially expressed genes in fat tissue of adult Berkshire and Jeju Native Pig using RNA-seq - Simrinder Singh Sodhi; Won Cheoul Park; Mrinmoy Ghosh; Jin Nam Kim; Neelesh Sharma; Kwang Yun Shin; In Cheol Cho; Youn Chul Ryu; Sung Jong Oh; Sung Hoon Kim; Ki-Duk Song; Sang Pyo Hong; et al. (Molecular Biology Reports, 2014)

Antimicrobial peptides in the centipede Scolopendra subspinipes mutilans - Won Gi Yoo; Joon Ha Lee; Younhee Shin; Jae-Young Shim; Myunghee Jung; Byeong-Chul Kang; Jaedon Oh; Jiyeon Seong; Hak Kyo Lee; Hong Sik Kong; Ki-Duk Song; Eun-Young Yun; et al. (Functional & Integrative Genomics, 2014)

Desulfotomaculum tongense sp. nov., a moderately thermophilic sulfate-reducing bacterium isolated from a hydrothermal vent sediment collected from the Tofua Arc in the Tonga Trench - In-Tae Cha; Seong Woon Roh; So-Jeong Kim; Hee-Ji Hong; Hae-Won Lee; Wan-Taek Lim; Sung-Keun Rhee (Antonie van Leeuwenhoek, 2013)

Characterization of SMV resistance of soybean produced by genetic transformation of SMV-CP gene in RNAi - Hye Jeong Kim; Mi-Jin Kim; Jung Hun Pak; Ho Won Jung; Hong Kyu Choi; Yeong-Hoon Lee; In-Youl Baek; Jong-Min Ko; Soon-Chun Jeong; In Sook Pack; Ki Hyun Ryu; Young-Soo Chung (Plant Biotechnology Reports, 2013)

Characterization of functional variants in 33 blood pressure loci using 1000 genomes project data - Ji Eun Lim; Young-Ah Shin; Kyung-Won Hong; Hyun-Seok Jin; In Song Koh; Bermseok Oh (Genes & Genomics, 2013)

Natural production of alkane by an easily harvested freshwater cyanobacterium, Phormidium autumnale KNUA026 - Jiwon Chang; Ji Won Hong; Hyunsik Chae; Han Soon Kim; Kyung Mok Park; Kyoung In Lee; Ho-Sung Yoon (Algae, 2013)

Sequence polymorphisms of Der f 1, Der p 1, Der f 2 and Der p 2 from Korean house dust mite isolates - Kyoung Yong Jeong; In-Yong Lee; Tai-Soon Yong; Jae-Hyun Lee; Eun-Jin Kim; Joo-Shil Lee; Chein-Soo Hong; Jung-Won Park (Experimental and Applied Acarology, 2012)

Phellinus baumii ethyl acetate extract inhibits lipopolysaccharide-induced iNOS, COX-2, and proinflammatory cytokine expression in RAW264.7 cells - Taddesse Yayeh; Won Jun Oh; Seung-Choon Park; Tae-Hwan Kim; Jae Youl Cho; Hwa-Jin Park; In-Kyoung Lee; Sang-Keun Kim; Seung-Bok Hong; Bong-Sik Yun; Man Hee Rhee (Journal of Natural Medicines, 2012)

A possible association of EMID2 polymorphisms with aspirin hypersensitivity in asthma - Charisse Flerida A. Pasaje; Jeong-Hyun Kim; Byung-Lae Park; Hyun Sub Cheong; Mi-Kyeong Kim; Inseon S. Choi; Sang Heon Cho; Chein-Soo Hong; Yong Won Lee; Jae-Young Lee; In Song Koh; Tae-Joon Park; et al. (Immunogenetics, 2011)

Environmental quality of Korean coasts as determined by modified Shannon–Wiener evenness proportion - Jae-Won Yoo; Yong-Woo Lee; Jennifer L. Ruesink; Chang-Gun Lee; Chang-Soo Kim; Mi-Ra Park; Kon-Tak Yoon; In-Seo Hwang; Jun-Ho Maeng; Rutger Rosenberg; Jae-Sang Hong (Environmental Monitoring and Assessment, 2010)

ENDOR and ESEEM investigation of the Ni-containing superoxide dismutase - Hong-In Lee; Jin-Won Lee; Tran-Chin Yang; Sa-Ouk Kang; Brian M. Hoffman (JBIC Journal of Biological Inorganic Chemistry, 2010)

Sulindac induces apoptotic cell death in susceptible human breast cancer cells through, at least in part, inhibition of IKKβ - A-Mi Seo; Seung-Woo Hong; Jae-Sik Shin; In-Chul Park; Nam-Joo Hong; Dae-Jin Kim; Won-Keun Lee; Wang-Jae Lee; Dong-Hoon Jin; Myeong-Sok Lee (Apoptosis, 2009)

Acute hypoxia induces vasodilation and increases coronary blood flow by activating inward rectifier K+ channels - Won Sun Park; Youn Kyoung Son; Nari Kim; Jae-Hong Ko; Sung Hyun Kang; Mohamad Warda; Yung E. Earm; In Duk Jung; Yeong-Min Park; Jin Han (Pflügers Archiv - European Journal of Physiology, 2007)

Hypoxia-induced cell death of HepG2 cells involves a necrotic cell death mediated by calpain - Min-Ju Kim; Soo-Jin Oh; Seong-Hoon Park; Hong-Jun Kang; Moo-Ho Won; Tae-Cheon Kang; In Koo Hwang; Jae-Bong Park; Jong-Il Kim; Jaebong Kim; Jae-Yong Lee (Apoptosis, 2007)

p53 and cell-cycle-regulated protein expression in small intestinal cells after fast-neutron irradiation in mice - Young-Heun Jee; Won-Il Jeong; Tae-Hwan Kim; In-Sun Hwang; Mee-Jung Ahn; Hong-Gu Joo; Su-Hyung Hong; Kyu-Shik Jeong (Molecular and Cellular Biochemistry, 2005)

Production of recombinant rotavirus VP6 from a suspension culture of transgenic tomato (Lycopersicon esculentum Mill.) cells - In Sik Chung; Chang Heon Kim; Kyung Il Kim; Seong Hyun Hong; Jong Hwa Park; Ju Kon Kim; Won Yong Kim (Biotechnology Letters, 2000)